Antimicrobial and antioxidant activities in ‘Beluntas’ (Pluchea indica), turmeric (Curcuma longa) and their mixtures - `Atiqah Ruqayyah Zabidi; Mohd Azmi Mohd Razif; Sayyidah Nafisah Ismail; Muhammad Widus Sempo; Nazariyah Yahaya (Penerbit Universiti Kebangsaan Malaysia, 2020)
Traditional medicine provides us essential guidance on herbal remedies with approaching health preservation methods. In this paper, we present the relevant prescriptions related to ‘Beluntas’ (Pluchea indica) and Turmeric (Curcuma longa) ingredients mentions in Malay Manuscript Code MSS 2802. In this study, antioxidant and antimicrobial properties in the mixture of P. indica and C. longa and their individual plants were studied based on prescription captured. Antimicrobial activities were performed against Staphylococcus aureus and Escherichia coli in vitro by micro dilution method and disk diffusion method. The observation from MIC and MBC show that the mixture of both plants has the highest ability to inhibit S. aureus followed by P. indica and C. longa. Meanwhile, at concentration of 2000 mg/mL, the inhibition zone of P. indica, C. longa, and mixture of both plants showed significantly different (p <0.05) with the values of 12.67±0.58, 6.33±0.58 and 10.16±0.58 mm, respectively. In this study, the antioxidant activities of P. indica, C. longa, and their mixture was measured the DPPH scavenging activity, FRAP and TPC. The DPPH scavenging activity showed that P. indica has significantly highest antioxidant ability among all the samples as it IC50 is the lowest with 379.822 µg/mL. In FRAP and TPC methods, P. indica also exhibited the significant highest antioxidant followed by their mixture and C. longa. In conclusion, this herb remedy may be considered as an alternative medicinal treatment that have competent antimicrobial and antioxidant properties. However, the formulation for the mixture of both plants need to further investigate.